Determination of the phenolic compounds profile by HPLC applied to the identification of adulteration markers of roasted and ground coffee by adding coffee husks - Lúcia Hulda de Sena Silva; Luzimar da Silva de Mattos do Nascimento; Manuela Cristina Pessanha de Araújo Santiago; Davy William Hidalgo Chávez; Cinthia de Carvalho Couto; Monalisa Santana Coelho de Jesus; Otniel Freitas-Silva; Sidney Pacheco; Renata Galhardo Borguini (Scientia Agricola)
ABSTRACT Coffee is a beverage that is widely consumed throughout the world, especially in Brazil. Its high market value makes it a prime target for fraud. To combat this fraud, different methods have been developed and improved over the years to detect potential adulterants in coffee and guarantee its authenticity. Nevertheless, these methods still pose a challenge. Therefore, this work aimed to identify adulteration markers in roasted and ground Arabica coffee using high-performance liquid chromatography (HPLC) to determine the flavonoid and phenolic acid profile. Samples of Arabica coffee beans and defective coffee beans were adulterated with coffee husks by preparing mixtures in different proportions (97:3, 90:10, 80:20 % w/w), which were then subjected to chromatographic and chemometric analyses, including principal component analysis (PCA) and partial least squares discriminant analysis (PLS-DA). Using the phenolic compounds associated with chemometric methods, protocatechuic acid was identified as a marker of adulteration in roasted and ground coffee with Arabica coffee husks, even at low adulterant concentrations (3 %).